Bargaining and Inequality in the Labor Market - Caldwell, Sydnee; Haegele, Ingrid; Heining, Jörg (Quarterly Journal of Economics, 2026)
We use novel surveys of firms and workers, linked to administrative employer-employee data, to study the prevalence and importance of individual bargaining in wage determination. We show that simple survey questions accurately elicit firms’ bargaining strategies. Using the elicited strategies for 772 German firms, we document that the majority of firms are willing to engage in individual wage bargaining. Labor market factors predict firms’ strategies better than firm characteristics. Survey responses from nearly 10,000 full-time workers indicate that most workers provide their salary expectations before they receive a job offer. Most outside offers are rejected, with the worker remaining at the incumbent firm. There is substantial heterogeneity in workers’ bargaining behavior, which translates into within-firm wage inequality. Firms that set pay via individual bargaining have a 3 percentage point higher gender wage gap.